Vaccine-induced inflammation and inflammatory monocytes promote CD4+ T cell-dependent immunity against murine salmonellosis. - Nancy Wang; Timothy A Scott; Andreas Kupz; Meghanashree M Shreenivas; Newton G Peres; Dianna M Hocking; Chenying Yang; Leila Jebeli; Lynette Beattie; Joanna R Groom; Thomas P Pierce; Linda M Wakim; et al. (PLoS Pathogens, 2023)
Prior infection can generate protective immunity against subsequent infection, although the efficacy of such immunity can vary considerably. Live-attenuated vaccines (LAVs) are one of the most effective methods for mimicking this natural process, and analysis of their efficacy has proven instrumental in the identification of protective immune mechanisms. Here, we address the question of what makes a LAV efficacious by characterising immune responses to a LAV, termed TAS2010, which is highly protective (80-90%) against lethal murine salmonellosis, in comparison with a moderately protective (40-50%) LAV, BRD509. Mice vaccinated with TAS2010 developed immunity systemically and were protected against gut-associated virulent infection in a CD4+ T cell-dependent manner. TAS2010-vaccinated mice showed increased activation of Th1 responses compared with their BRD509-vaccinated counterparts, leading to increased Th1 memory populations in both lymphoid and non-lymphoid organs. The optimal development of Th1-driven immunity was closely correlated with the activation of CD11b+Ly6GnegLy6Chi inflammatory monocytes (IMs), the activation of which can be modulated proportionally by bacterial load in vivo. Upon vaccination with the LAV, IMs expressed T cell chemoattractant CXCL9 that attracted CD4+ T cells to the foci of infection, where IMs also served as a potent source of antigen presentation and Th1-promoting cytokine IL-12. The expression of MHC-II in IMs was rapidly upregulated following vaccination and then maintained at an elevated level in immune mice, suggesting IMs may have a role in sustained antigen stimulation. Our findings present a longitudinal analysis of CD4+ T cell development post-vaccination with an intracellular bacterial LAV, and highlight the benefit of inflammation in the development of Th1 immunity. Future studies focusing on the induction of IMs may reveal key strategies for improving vaccine-induced T cell immunity.